Beyond the posterior tibial slope: Rethinking anterior cruciate ligament (ACL) re‐rupture risk through integrated scoring: Introducing the ACL + slope tracing risk‐factor algorithm (A + STRA) score: A personalised, risk‐based approach to optimising ACL revision strategy - Ollivier, Matthieu; Mabrouk, Ahmed; Parratte, Sebastien; Kley, Kristian; Hirschmann, Michael T. (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2025)
Anterior cruciate ligament (ACL) graft failure remains a relevant challenge, particularly in revision settings where anatomical and clinical risk factors converge to an increased retear risk. Posterior tibial slope (PTS) is a well‐established biomechanical contributor. Each degree of increased PTS leads to greater anterior tibial translation (ATT) and higher ACL graft strain. Nevertheless, current decision‐making frameworks often consider PTS in isolation and may underappreciate important patient‐specific risk factors. To address this gap, the A + STRA score (ACL + slope tracing risk‐factor algorithm), a pragmatic, stratified system is proposed. The A + STRA score integrates medial posterior tibial slope (MPTS) measured on long‐leg lateral radiographs with individual clinical risk and limiting factors to guide the use of slope‐correcting osteotomy (SCO) in ACL reconstruction. The algorithm is structured around four key elements: (1) degree of posterior tibial slope, (2) surgical context (primary vs. revision), (3) cumulative risk factors for graft failure and (4) potential limiting factors that may contraindicate SCO. PTS thresholds are dynamically adjusted according to revision burden and further modified by additive or subtractive scores for risk and limiting variables. A threshold of >13° on long‐leg radiographs was selected, accounting for the approximately 2° overestimation reported with this modality compared to standard short‐leg radiographs. The A + STRA Score assigns weighted values to risk factors (e.g., medial meniscus integrity, static anterior tibial translation [sATT] > 10 mm, contralateral ACL injury, revision status) and limiting factors (e.g., tunnel malposition, recurvatum, prior infection and professional athletic status). The summed score is plotted against PTS to yield individualised surgical recommendations, ranging from isolated ACL reconstruction to combined SCO and lateral extra‐articular tenodesis. High scores (≥10) indicate slope correction regardless of the PTS value. To demonstrate the clinical applicability and enhance understanding of the algorithm's utility, a series of case scenarios is presented, reflecting a wide spectrum of anatomical and clinical profiles. These cases illustrate how the A + STRA Score can guide real‐world surgical decision‐making in complex ACL reconstructions.